Autoantibodies Profile in the Sera of Patients with Sjogren]s Syndrome: The ANA Evaluation—A Homogeneous, Multiplexed System - Boris Gilburd; Mahmoud Abu-Shakra; Yehuda Shoenfeld; Andrea Giordano; Elena Bartoloni Bocci; Francesco delle Monache; Roberto Gerli (Clinical and Developmental Immunology)
Background: Flow-based, multiplex bead arrays (MBA) have been developed for a variety of applications including the detection of antibodies to extractable nuclear antigens (ENA). It offers a rapid and sensitive method to assess multiple analyses in a single tube/well.